On energy transfer phenomena, in a nonlinear ideal and nonideal essential vibrating systems, coupled to a (MR) magneto-rheological damper - Tusset, Angelo Marcelo; Balthazar, José Manoel [UNESP]; Chavarette, Fábio Roberto; Palacios Felix, Jorge Luis (Springer, 2012)
In this paper, a control strategy is applied to a nonlinear ideal and nonideal vibrating system coupled to a magneto-rheological damping structure, exhibiting chaotic behavior. In order to suppress the chaotic oscillations and to improve the transient response, a combination of passive (energy pumping) and active (state feedback) control strategies. The chaotic vibrations are suppressed, bringing the system to a desired periodic orbit. Additionally, the control damping force is transformed into the electrical control signal variable.
Keywords: Ideal and nonideal structure; Nonlinear dynamics; Optimal linear control; Magneto-rheological damper; Energy pumping (transfer)